STRUKTUR KOMUNITAS PLANKTON KERAMBA JARING APUNG DI TELUK LAMPUNG - Gres Maretta; Desri Yohanna Christiani Nainggolan; Andy Darmawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Plankton is the most important component in aquatic life which plays an important role as the earliest link in the food chain. Plankton into two, namely animal plankton is referred to as zooplankton and plant plankton is referred to as phytoplankton. The purpose of this study was to determine the structure of the plankton community in floating net cages (KJA). The research was carried out in February-April 2022 in the waters of the Floating Net Cages in Lampung Bay. The method used is purposive sampling method. Sampling was carried out based on stations, namely station 1 (located at a location with a higher number of KJA), station 2 (located at a location with a smaller number of KJA), station 3 (located at a location where there were no KJA). The data obtained were analyzed for Diversity and Dominance. The highest diversity index was found at station 3 which reached 3,26 at station 3, while the highest dominance index value reached 0,047 at station 2. The number of species found in floating net cages was 29 genera, 17 phytoplankton and 12 genera of zooplankton . The dominant phytoplankton is Skeletonema and the dominant zooplankton is Naupilus.